142 ACGIH Threshold Limit Values® (TLV®s) established from 2008-2018 lack consistency and transparency. (31st January 2019) - Smith, Carr J; Perfetti, Thomas A
The American Conference of Governmental and Industrial Hygienists (ACGIH ® ) states "…the TLV ® -CS Committee preferably relies on published, peer-reviewed literature available in the public domain." Many studies used to document threshold limit values (TLVs) are not peer reviewed, with many unpublished. The academic studies published in the peer-reviewed literature upon which ACGIH relies to determine TLVs rarely report data not already statistically transformed and thus incalculable. From 2008 to 2018, ACGIH established or reviewed TLVs for 145 different substances or groups of substances. Studies underlying development of these 145 TLVs demonstrate limited reporting of data sufficient to facilitate independent statistical analysis. None of the 145 TLVs showed sufficient data to independently substantiate ACGIH's evaluations. In the majority of cases, sentinel studies upon which calculation of the TLV was based cannot be determined. Occupational Safety and Health Administration (OSHA) recommends workplaces rely on ACGIH TLVs and National Institute for Occupational Safety and Health recommended exposure limits rather than older OSHA permissible exposure limit values to optimize worker safety. Inaccurate or poorly substantiated determination of TLVs can adversely affect both human health and commerce, as net US sales of the 145 substances represent an estimated USD$189 billion, about one-fourth of the USD$800 billion chemical market in the United States. ACGIH should provide the studies relied upon, individual data values supporting the TLVs, and statistical calculation methods underlying the development of a TLV. The current system of poorly supported and underreported TLVs has the potential to propagate errors into the standard setting process of other regulatory organizations both nationally and internationally, as the ACGIH TLVs are used by many foreign regulatory bodies. Increased transparency by ACGIH is consistent with recent reforms implemented by US EPA.